2017
DOI: 10.1016/j.athoracsur.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Furosemide Responsiveness Predicts Acute Kidney Injury in Infants After Cardiac Surgery

Abstract: After correcting serum creatinine for fluid balance and adjusting for surgical complexity, LFR performs fairly at 2 hours, whereas at 6 hours, LFR is a good AKI predictor. Prospective studies are needed to validate whether diuretic responsiveness predicts AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Patients with AKI have reduced response to furosemide, and lack of furosemide responsiveness is predictive of AKI development in children undergoing cardiac surgery 160,161 . In adults, unresponsiveness in a furosemide stress test (urine output below 200 mL in 2 h after treatment with 1 mg/kg intravenous furosemide in furosemide-naive patients or 1.5 mg/kg in patients who had received furosemide within the past 7 days) identifies patients at high risk for AKI progression and subsequent use of RRT 145 .…”
Section: Human Albumin Solution For Renal Protectionmentioning
confidence: 99%
“…Patients with AKI have reduced response to furosemide, and lack of furosemide responsiveness is predictive of AKI development in children undergoing cardiac surgery 160,161 . In adults, unresponsiveness in a furosemide stress test (urine output below 200 mL in 2 h after treatment with 1 mg/kg intravenous furosemide in furosemide-naive patients or 1.5 mg/kg in patients who had received furosemide within the past 7 days) identifies patients at high risk for AKI progression and subsequent use of RRT 145 .…”
Section: Human Albumin Solution For Renal Protectionmentioning
confidence: 99%
“…articles were screened based on their titles and abstracts in order to identify the potentially relevant articles, the full texts of which then were downloaded and reviewed to further determine their eligibility for inclusion in the final analysis. Of the 29 articles, two [32,33] was suspected of using a duplicate cohort from another study [8], five were focused on child populations [11,12,[34][35][36], and three were based on kidney transplant outcomes [9,10,37]. Meanwhile, five studies reported different outcomes of interest and the remaining three did not report sufficient information for analysis [38][39][40][41][42][43][44][45] (Additional profile 1: Supplementary Table 2).…”
Section: Literature Searchmentioning
confidence: 99%
“…Several following studies also utilized FST to predict AKI progression or RRT prediction, but with heterogeneity in AKI criteria, cut-off value of urine output, duration of monitor or study designs. A few recent studies used FST to predict delayed graft function after kidney transplant [9,10], and others focused on child populations [11,12]. As such, in order to more effectively explore the diagnostic accuracy of the FST to predict AKI progression and RRT initiation, we conducted this meta-analysis according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagnostic test accuracy guidelines [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined whether lack of post-operative diuretic responsiveness has utility as an early acute kidney injury predictor according to modified kidney disease improving global outcomes criteria. 38,39 The Neonatal and Paediatric Heart and Renal Outcomes Network collects hourly urine output for the first 8 hours after initial diuretic administration. This will permit a more detailed examination of diuretic responsiveness and acute kidney prediction among the 1162 subjects receiving furosemide within the first 24 post-operative hours.…”
Section: Diuretic Responsiveness Predict Post-operative Cardiac Surgementioning
confidence: 99%